Pengaruh Perceived Value, Brand Image, dan Trust Terhadap Loyalitas Pelanggan - Yustinus Ericko Kelvianto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this research is to understand the effect of perceived value, brand image, and trust to Customers' Loyalty. The research design is based on descriptive method and the data was collected through primary data with five Likert-Scales questionaire. The samples of this research are customer who use one of the LCC flight service at least 2 times in 3 months. Convenience sampling method was used in order to gather data. Out of 200 questioners, 167 questioners were computed with SPSS to give the results. This research about The Effect of Perceived Value, Brand Image, and Trust to Customers' Loyalty can be concluded that Customers' loyalty is affected positively by the perceived value, brand image, and trust. Thus, the company should improve their perceived value, brand image, and trust to maintain and increase their customer's loyalty.